The Analysis of 2D Crowd Behaviour Simulation during Emergency Situation - Hamizan, Binti Sharbini; Azlina, Binti Ahmadi Julaihi; Tan, Ping Ping; Chiu, Po Chan; Noor Alamshah, Bolhassan; Cheah, Wai Shiang; Nur Aisyah, Binti Masrizal (2019)
This paper will discuss about general crowd behaviour modeling during evacuation in emergency situation such as during fire breakout. Several existing simulation tools and comparison among each tool will also be discussed. The aim of this project is to develop a generic crowd model, which has the ability to demonstrate individual crowd behaviours (micro level) especially in fire emergency situation with one or more exits. The program will be able to estimate the evacuation time of panic situation during fire breakout. Apart from that, this paper also will analyze and prove that the individual agent in the simulation is able to detect and avoid collision. During panic situation, agents need to search for the exit in order to save themselves from danger. The proposed crowd simulation used agent in 2D as to simulate the crowd behaviour model while steering towards the exit.